The Effect of Corruption in the Mining Sector on State and Environmental Losses (Case Study of PT Timah Tbk) - Muhammad Aras Prabowo; Dika Dermawan; Fitria Auldri Desiana; Fira Mubayyinah (Innovation Business Management and Accounting Journal, 2024)
The purpose of this research is to determine the problem of the influence of PT Timah corruption on state and environmental losses. The research method used in this research is the literature method, by obtaining research from various sources, with steps such as determining a problem or describing subtopics , looking for sources from previous research, and rearranged it so that it becomes new research. The results of this research show corruption cases involving PT. Timah (Tbk) has shown how illegal and unethical practices in natural resource management can cause huge losses to the country and society. Corruption that occurred at PT. Timah (Tbk) not only resulted in financial losses of 271 trillion rupiah, but also caused significant damage to the environment. This highlights the urgent need for stricter governance, transparency, and accountability in the management of natural resources to prevent further harm to the environment and economic stability.